The ubiquitin-like (UBX)-domain-containing protein Ubx2/ Ubxd8 regulates lipid droplet homeostasis - Wang, Chao-Wen; Lee, Shu-Chuan (Journal of cell science, 2012)
Lipid droplets (LDs) are central organelles for maintaining lipid homeostasis. However, how cells control the size and number of LDs remains largely unknown. Herein, we report that Ubx2, a UBX-domain-containing protein involved in endoplasmic reticulum (ER)-associated degradation (ERAD), is crucial for LD maintenance. Ubx2 redistributes from ER to LDs when LDs start to form and enlarge during diauxic shift and in the stationary phase. ubx2Δ cells contain abnormal number and reduced size of LDs and their triacylglycerol (TAG) is reduced to 50% of the normal level. Deletion of either UBX or UBA domain in Ubx2 has no effect, but deletion of both causes LD phenotypes similar to that in ubx2Δ. The reduced TAG in ubx2Δ is likely due to mislocalization of Lro1, one of the two TAG-synthesizing enzymes in yeast, which moves along the ER and distributes dynamically to the putative LD assembly sites abutting LDs. Thus, Ubx2 is important for the maintenance of cellular TAG homeostasis likely through Lro1. The mammalian Ubxd8 expressed in yeast complements the defect of ubx2Δ, implying a functional conservation for these UBX-domain-containing proteins in lipid homeostasis.